PERCEPTIONS ABOUT TREATMENT OF PSYCHIATRIC DISORDERS BY FAITH HEALERS/ PSYCHIATRISTS AMONG GENERAL PUBLIC OF URBAN AND RURAL AREAS OF RAWALPINDI DISTRICT - Shah, Hassan Bin Usman; Atif, Iffat; Nabeel, Muhammad; Qureshi, Hammad; Sadiq, Subhan Mansoor; Ahmed, Waqar; Raheem, Abdul; Bukhari, Haseeb (Journal of Ayub Medical College Abbottabad, 2018)
Background: With the passage of time, there has been a drastic increase in psychiatric disorders in past few decades across the world. Due to lack of education and awareness in the rural community, a majority of people still have strong misconceptions about the causation of psychiatric disorders and hence serve as a barrier for their medical treatment. Methods: A comparative cross-sectional study was conducted in the urban and rural areas of Rawalpindi district from March 2015 to August 2015, to find out the perception about treatment of psychiatric disorders among general public. Structured closed ended questionnaire was used to collect data from the participants and the results were analysed using SPSS. Chi square test was used to determine the association between categorical variables among urban and rural areas. Results: The finding of our study confirmed that people of urban areas tend to choose and seek treatment by psychiatrists more (74%) as compared to those living in rural area who tend to select and believe in methodology and treatment provided by faith healers (55%). Lack of education, poor socioeconomic status, high treatment cost and most importantly false beliefs were the major contributory factors for people of rural areas in their inclination towards faith healers. Conclusion: The study concluded that most of the people of rural areas seek and trust the treatment by faith healers more as compared to psychiatrists. The importance of education and insight for the disorder cannot be denied for proper decision making about treatment choices. Keywords: Perceptions; Psychiatric disorders; Faith healers, Psychiatrists